A grounded theory study of the identity and career decisions of artistic creative entrepreneurs - Gibson-Tessendorf, Jacoba Cornelia (Rhodes University, Faculty of Commerce, Rhodes Business School)
This research, in the field of creative careers, identity and entrepreneurship, aims to develop a grounded theory to explain the interaction between the phenomena of identity and career decision-making, focusing on Artistic Creative entrepreneurs in the creative industries. Artistic Creatives have unique characteristics and creative identities, presenting unique career opportunities. This research is interested in the different values of Artistic Creatives compared to those of Artistic Creative Entrepreneurs, who often experience a tension between their creative identity and their entrepreneurial identities The methodology used is the Straussian Grounded Theory. A Qualitative Research Approach used interviews to collect data on the careers and identity of Artistic Creative entrepreneurs in an area in the Eastern Cape Province of South Africa. Creative entrepreneurs work in the fields of fine art, design and crafts. The research procedure was recorded in detail, which enhances dependability. Ethics approval was obtained prior to the data collection. The data was analysed through open coding, axial coding and using a Straussian paradigm model. The findings present the values and identity of the Artistic Creative with Artistic Creative Archetypes and the entrepreneurial identities as Artistic Creative Entrepreneur Profiles. The Thesis by JC Gibson-Tessendorf effects of identity and contextual factors on their career patterns, especially as entrepreneurs, are analysed. The contribution that this study makes towards the creation of new knowledge is through, firstly, presenting aspiring creatives with career opportunities that relate to individual values. Secondly, it provides a model of Career Stage Options and Strategies that Artistic Creative Entrepreneurs may follow to either become part-time creative entrepreneurs or use the model as a guide for career planning. The study also developed a substantial theory proposing that the identities of Artistic Creative Entrepreneurs are 1) firstly multiple, 2) flexible and open to change, 2) driven by their values, 3) enacting across the tripartite identity framework, being personal identity, role identity and social identity. The concept of a tripartite of identities was taken from Brewer and Gardner (1996).
Keywords: Entrepreneurship; Creative entrepreneurship; Personality and creative ability; Career choice; Creative industries; Identity (Psychology)